Interleukin‐6 signaling requires EHD1‐mediated alteration of membrane rafts. (27th April 2022) - Woo, Joo Hong; Park, Soo Jung; Park, Sang Myun; Joe, Eun‐hye; Jou, Ilo
Abstract : Interleukin‐6 (IL‐6) is involved in many inflammatory diseases. IL‐6 binds to membrane‐bound IL‐6 receptor α (IL‐6Rα) (classic signaling) or soluble IL‐6Rα (trans‐signaling); this complex then associates with the signal‐transducing membrane protein gp130. IL‐6Rα and gp130 float on membrane (i.e., lipid) rafts; however, how membrane rafts regulate IL‐6 signaling remains unclear. Here, we demonstrate that both IL‐6 classic signaling and trans‐signaling depend on membrane cholesterol, an essential raft component. Super‐resolution fluorescence imaging using perfringolysin O D4 fragments that selectively bind to high cholesterol concentrations revealed that IL‐6 and hyper‐IL‐6, a fusion protein of IL‐6 and soluble IL‐6Rα, induce the alteration of membrane rafts. IL‐6 and hyper‐IL‐6 induced D4‐positive raft (D4 raft) formation without affecting cholera toxin subunit B (CTB)‐positive rafts (CTB rafts). Receptor clustering of IL‐6Rα and gp130 and STAT3 phosphorylation occurred in D4 rafts. These results indicate that D4 rafts serve as platforms for the assembly of functional IL‐6 receptor complexes. We found that Eps15 homology domain‐containing protein 1 (EHD1) mediates the formation of functional IL‐6 receptor complexes through D4 rafts. Overall, we uncover a novel regulatory mechanism of the EHD1‐mediated alteration of membrane raft in IL‐6 signaling. Abstract : Both IL‐6 classic and trans‐signaling depend on membrane cholesterol and induce the alteration of membrane rafts. IL‐6 receptor clustering and STAT3 phosphorylation occur in D4 rafts, which serve as platforms for IL‐6 receptor assembly. EHD1 mediates the formation of functional IL‐6 receptor complexes through D4 rafts.